2006
DOI: 10.1196/annals.1346.023
|View full text |Cite
|
Sign up to set email alerts
|

Role of Connexin43 in Osteoblast Response to Physical Load

Abstract: Gap junctions are hexameric transmembrane channels formed by connexins, and are responsible for direct cell-to-cell communication. The most abundant gap junction protein in bone is connexin43 (Cx43), although connexin45 (Cx45) is also expressed. In the present study, we tested the hypothesis that bone cell responses to mechanical stimulation are dependent on the type of gap junction communication provided by Cx43 in vitro and in an in vivo model of physical load. Application of cyclic stretch to calvaria osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 31 publications
7
33
1
Order By: Relevance
“…3,6,7 This bioreactor has applied 5%-10% elongation with 0.2-1 Hz frequency to 3D scaffolds including polyurethane nanofibrous scaffolds, 8 and fibrin, 9 and collagen gels. 10 Tensile stress of 3%-20% magnitude modulated expression of bone-related molecules such as collagen, 7,11 osteocalcin (OCN), 1,7 osteopontin (OPN), 1,7 matrix metalloproteinase-13 (MMP-13), 12 osteoprotegerin (OPG), 6 prostaglandin E 2 (PGE 2 ), 13 cyclooxygenase-2 (COX-2), 14 vascular endothelial growth factor (VEGF), 1,15 and transforming growth factor-b1 (TGF-b1). 16 Other external stimulating factors for bone regeneration are osteoinductive growth factors (GFs) such as TGF, bone morphogenetic protein (BMP), and platelet-derived GF.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,7 This bioreactor has applied 5%-10% elongation with 0.2-1 Hz frequency to 3D scaffolds including polyurethane nanofibrous scaffolds, 8 and fibrin, 9 and collagen gels. 10 Tensile stress of 3%-20% magnitude modulated expression of bone-related molecules such as collagen, 7,11 osteocalcin (OCN), 1,7 osteopontin (OPN), 1,7 matrix metalloproteinase-13 (MMP-13), 12 osteoprotegerin (OPG), 6 prostaglandin E 2 (PGE 2 ), 13 cyclooxygenase-2 (COX-2), 14 vascular endothelial growth factor (VEGF), 1,15 and transforming growth factor-b1 (TGF-b1). 16 Other external stimulating factors for bone regeneration are osteoinductive growth factors (GFs) such as TGF, bone morphogenetic protein (BMP), and platelet-derived GF.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies involving mesenchymal stem cells have shown that biaxial strain promoted osteogenic differentiation [51,53]. Larger strains seemed to cause differentiated cells to de-differentiate and proliferate, while guiding undifferentiated cells to an osteogenic state [51,53,54].…”
Section: In-vitro Modelsmentioning
confidence: 98%
“…For the study of highly specific research questions about the healing process of bone, in-vitro models are very relevant [51,53,54]. Most of the progress in these experiments stem from examining the mechanical sensitivity of bone healing in 2D cell culture systems [51,53].…”
Section: In-vitro Modelsmentioning
confidence: 99%
See 2 more Smart Citations